Young Autism Spectrum Disorder Children in Special and Mainstream Education Settings Have Similar Behavioral Characteristics. Issue 4 (1st October 2020) - Ilan, Michal; Meiri, Gal; Manelis‐Baram, Liora; Faroy, Michal; Michaelovski, Analya; Flusser, Hagit; Binoun‐Chaki, Hagar; Segev‐Cojocaru, Ronit; Dotan, Orly; Schtaierman, Hen; Menashe, Idan; Dinstein, Ilan
Abstract : In many countries, parents can place autism spectrum disorder (ASD) children in either mainstream or special education settings, which differ in their ability to provide structured early intervention programs. There are no clear guidelines for how to make initial placement decisions and ongoing debate about the benefits and drawbacks of each educational setting. Previous studies have mostly examined placement of school‐age children and reported that those with poorer cognitive abilities and more severe ASD symptoms tend to be placed in special education. The placement of younger children has rarely been studied. Here, we utilized the database at the National Autism Research Center of Israel to examine whether ASD severity, cognitive abilities, and parent education influenced the placement of 242 children. We performed the analyses separately for 1–3‐year‐old children who were placed in daycare centers and 3–5‐year‐old children who were placed in pre‐school kindergartens. Our analyses revealed surprisingly small differences across special and mainstream education settings, particularly in daycare centers. Cognitive scores and parent education were significantly higher in ASD children placed in mainstream education, but these differences were of moderate effect size and explained a relatively small percentage of the variability in placement choices (<15%). Indeed, we found considerable overlap in the characteristics of ASD children across educational settings, which suggests that initial placement decisions are performed with little regard to the children's abilities. Given the importance of optimal early intervention, further studies are warranted to determine whether children with specific abilities and needs benefit more from placement in either educational setting. Lay Summary: Currently, there are no clear recommendations for placing young children with ASD in special versus mainstream education settings. We examined the influence of ASD severity, cognitive abilities, and parent education on the initial placement of 242 children. While we found significantly higher cognitive scores and parental education in children placed in mainstream education, there was a remarkable overlap in the characteristics of children across both settings, suggesting that initial placement is performed with limited regard to the children's abilities. Autism Res 2021, 14: 699–708 . © 2020 International Society for Autism Research and Wiley Periodicals LLC